Effect of the probiotic Saccharomyces cerevisiae on ligature-induced periodontitis in rats - Garcia, V. G. [UNESP]; Knoll, L. R.; Longo, M.; Novaes, V. C. N.; Assem, N. Z.; Ervolino, E.; Toledo, B. E. C. de; Theodoro, L. H. (Wiley-Blackwell, 2015)
This study assessed the effects of the local use of Saccharomyces cerevisiae as monotherapy and as an adjuvant to the mechanical treatment of ligature-induced periodontitis in rats. Periodontitis was induced in 72 rats via the installation of a ligature around the mandibular first molar. After 7 d, the ligature was removed and the rats were placed in one of the following groups: no treatment (C; n = 18); scaling and root planing (SRP; n = 18); local irrigation with probiotics (PRO; n = 18); and SRP followed by local irrigation with probiotics (SRP/PRO; n = 18). Six rats from each group were killed at 7, 15 and 30 d. The histological characteristics, alveolar bone loss (ABL) and immunolabeling of tumor necrosis factor alpha (TNF-α), interleukin-1beta (IL-1β), interleukin-10 (IL-10) and TRAP on the furcation area of the first molar were assessed. The PRO group showed features of acceleration of the tissue-repair process during the entire experiment. On day 15, there was less ABL in the SRP/PRO group compared with the C group. There were fewer TRAP-positive cells in the SRP and SRP/PRO groups at 30 d. There was less immunostaining for TNF-α in the PRO and SRP/PRO groups and less immunostaining for IL-1β in the PRO group. However, there was more immunostaining for IL-10 in the PRO group on day 15. Local use of the probiotic did not result in any adverse effects on periodontal tissues. When used as monotherapy or as an adjuvant, the probiotic was effective at controlling periodontitis in rats.
Keywords: Alveolar bone loss; Periodontitis; Probiotics; Rats